PENDIDIKAN SEKS TERHADAP WANITA MENURUT TRADISI JAWA DI PEDESAAN - Farida Hanum (Jurnal Penelitian Humaniora, 2007)
Problem of sex in Javanese society seems to be taboo to talk, especially between parents to children. This research views the depiction and digs information about sex education in Javanese family in villages in DIY. The informants of this research are parents who have young adult children (male and female) in villages I Sleman, Bantul, Gunungkidul, and Kulon Progo. Information is gained through in-depth interview with the informants. Triangulation is used to keep the data valid. The research result shows that parents think that sex education is needed. Most of them think that sex education is best given by teachers in school, especially teachers of religions. Some think that children will understand by themselves automatically as they grow, perhaps from their friends or neighbors